Simulation of morphology for oil droplets in aqueous solution controlled by electric fields - Heping Wang; Yinchao Lin; Yanggui Li; Xiaohang Zhang; Yi Wu (Heliyon, 2023)
This study investigate the morphology of oil-in-water at high density ratio controlled by electric field. We incorporated the electric field into the Lattice Boltzmann method (LBM). The focus is on the modified lattice Boltzmann color gradient model simulate the evolution of the oil-in-water and analyze the relation between morphologies and electric field parameters. The results show that the stretching, merging and even breaking can be regulated by electric field strength, conductivity, dielectric constant, oil-water density ratio and droplet radius. Simulation results showed that the larger dielectric constant resulted in the smaller deformation, and the larger conductivity related to the greater deformation. Meanwhile, the larger radius droplet is easier to deform and break, and the higher density droplet is less likely to break. And this paper also gives the morphology of the stretching and destabilization of the droplets at each stage. These results are in good agreement with the relevant theoretical and experimental results.